Dissatisfaction with own body makes patients with eating disorders more sensitive to pain - Yamamotova, Anna; Bulant, Josef; Bocek, Vaclav; Papezova, Hana (Journal of pain research, 2017)
Body image represents a multidimensional concept including body image evaluation and perception of body appearance. Disturbances of body image perception are considered to be one of the central aspects of anorexia nervosa and bulimia nervosa. There is growing evidence that body image distortion can be associated with changes in pain perception. The aim of our study was to examine the associations between body image perception, body dissatisfaction, and nociception in women with eating disorders and age-matched healthy control women. We measured body dissatisfaction and pain sensitivity in 61 patients with Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition diagnoses of eating disorders (31 anorexia nervosa and 30 bulimia nervosa) and in 30 healthy women. Thermal pain threshold latencies were evaluated using an analgesia meter and body image perception and body dissatisfaction were assessed using Anamorphic Micro software (digital pictures of their own body distorted into larger-body and thinner-body images). Patients with eating disorders overestimated their body size in comparison with healthy controls, but the two groups did not differ in body dissatisfaction. In anorexia and bulimia patient groups, body dissatisfaction (calculated in pixels as desired size/true image size) correlated with pain threshold latencies (r=0.55, p=0.001), while between body image perception (determined as estimation size/true image size) and pain threshold, no correlation was found. Thus, we demonstrated that in patients with eating disorders, pain perception is significantly associated with emotional contrary to sensory (visual) processing of one's own body image. The more the patients desired to be thin, the more pain-sensitive they were. Our findings based on some shared mechanisms of body dissatisfaction and pain perception support the significance of negative emotions specific for eating disorders and contribute to better understanding of the psychosomatic characteristics of this spectrum of illnesses.
Keywords: bulimia nervosa; body dissatisfaction; body image perception; pain perception; anorexia nervosa; Anamorphic Micro